The Utilization of Smartphone Applications in Enabling Community Health Volunteer to Prevent Child Marriage - Darmawati, Irma; Dharmansyah, Dhika (Universitas Nahdlatul Ulama Surabaya, 2024)
yet psychologically and socially prepared to form a family. Preventing child marriage necessitates the active involvement of community health volunteers as agents of change in society. Objective : The purpose of community service is to implement PEDE smartphone application for health promotion among community health voluenteer. Methods: The activities are conducted comprehensively to build skills among community health volunteers in addressing the phenomenon of child marriage in society. The implementation of services is carried out through training and mentoring to enhance both soft and hard skills of community health volunteers in preventing child marriage. The activities are divided into three stages: (1) introducing the PEDE’s application, (2) practical simulation of health education for adolescents, and (3) evaluation of the improvement of life skills among workers. Results: The utilization of PEDE’s smartphones application facilitates active engagement and improve the understanding of community health volunteers. Conslusion : This activities enhance community health volunteers' attitudes toward child marriage and ultimately contribute to the prevention of this social issue.